PERAN CHEF DALAM MENINGKATKAN KINERJA MAIN KITCHEN DI HOTEL FOX PEKANBARU - Patricia, Siska; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The main kitchen is the main kitchen in a hotel, but in hotel operations the kitchen plays a very important role, because the main task of the kitchen is to process food and drinks, from raw ingredients until they are ready to be served to guests. Based on the pre-survey that has been carried out, to date there are still problems that arise due to several chef performance factors including: Food that is not salty enough/too salty, the food menu is just ordinary, food is served late, drinks are not sweet enough, service takes a long time. The method used in this research is descriptive qualitative research. The subjects in this research were 3 people, including 2 chefs and 1 customer. Data collection techniques use interviews, observation and documentation. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. The research results show that in improving the performance of the Main Kitchen chef at FOX Hotel Pekanbaru, he has various abilities in an effort to improve performance at FOX Hotel Pekanbaru, including: 1. Core abilities: a) Improving cleanliness, b) Understanding tasks, c) Carrying out job evaluations, d) Prepare menus. 1. Personal abilities: a) Building work relationships, b) Managing work time. 3) Ability to overcome external problems: a) Ability to overcome obstacles, b) Handle complaints, c) Deal with pressure Keywords:Chef Role, Performance.